Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Terhadap Peningkatan Hasil Belajar Siswa Pada Bencana Letusan Gunung Berapi Melalui Strategi Role Playing Di SMA Negeri 2 Klaten - TRISMAWATI, Diana, Drs. Rubino Rubiyanto, M.Pd (2016)
The application of role playing in this research is aims to describe the effectiveness from teaching material of learning guilding book about disaster in Klaten regency on the explosion of mountain material which is show by the increasing of the student learning result. This research has done in Senior High School 2 Klaten, which is located in the west Klaten, 25 km from Merapi mountains peak, Yogyakarta. The research method which is used is experiment with pre test post test control group design. The sample is X MIPA 4 with 25 students as the experiment class and X MIPA 5 with 25 students as the control class. Learning on the experiment class is using role playing strategy, while on the control class is using conventional strategy with taking data by pre test post test question which has given in the both class. The technique of data analysis which is used is paired samples t test to know whether it has different result. The result of data tabulation which is get showed that there are the increasing of the students result on the experiment class from 56,32 % to 86,56% and the control class from 53,92% to 67,84%. So it can conclude that teaching material of learning guilding book about disaster in Klaten regency is effective which is showed by the increasing of study result by role playing strategy is bigger than conventional, that is increasing as much as 30,24 %.